Parametrization of gamma-ray production cross sections for p p interactions in a broad proton energy range from the kinematic threshold to PeV energies - Kafexhiu, Ervin (2014)
Using publicly available Monte Carlo codes as well as compilation of published data on p--p interactions for proton kinetic energy below 2 GeV, we parametrize the energy spectra and production rates of γ-rays by simple but quite accurate (≤20%) analytical expressions in a broad range from the kinematic threshold to PeV energies.